Research on continuous granular material flow detection method and sensor. (September 2021) - Jiang, Meng; Liu, Cailing; Du, Xin; Huang, Rongbiao; Dai, Lei; Yuan, Hao
Graphical abstract: Highlights: A photoelectric method for measuring fertilizers and seeds flow is proposed. The real-time flow rate of seeds and fertilizers has a strong correlation with the sensor voltage. The accumulation method and sorting method to build the measuring models are compared. The experimental investigation confirms the potential of the method for the measurement of seeding and fertilization flow. Abstract: The flow rate measurement of seeding and fertilization is the premise for precise control; it's difficult to measure accurately due to the particles flow in a continuous dense state. A flow rate measuring method based on the correlation between the sensor voltage and particles flow rate was introduced. Two algorithms for models building were proposed. To demonstrate the feasibility of this method and evaluate the accuracy of the algorithms, a particles flow rate sensor and test bench were designed. Wheat, rice, compound fertilizer, and urea were chosen as the experimental subject. The result showed that it has a strong correlation between the voltage and flow rate. The R 2 fitted by accumulation method (AM) for the four materials were 0.9998, 0.9984, 0.9999, and 0.9998, and the R 2 of sorting method (SM) were 0.9934, 0.9843, 0.9903, and 0.9928. The statistics showed the measurement accuracy of AM was higher than that of SM.